2017
DOI: 10.1177/1179172117721902
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmology in North America: Early Stories (1491-1801)

Abstract: New World plants, such as tobacco, tomato, and chili, were held to have beneficial effects on the eyes. Indigenous healers rubbed or scraped the eyes or eyelids to treat inflammation, corneal opacities, and even eye irritation from smoke. European settlers used harsh treatments, such as bleeding and blistering, when the eyes were inflamed or had loss of vision with a normal appearance (gutta serena). In New Spain, surgery for corneal opacity was performed in 1601 and cataract couching in 1611. North American p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…In the early 18th century, Benjamin Franklin reported that patients who were struck by lightning developed rapidly progressing cataracts, which ultimately resulted in blindness. 7 Despite this report, electric and magnetic therapy was practiced in London for the treatment of patients with cataract in 1779. 7 In 1887, Elliot Colburn, professor of ophthalmology and otology in the Chicago Policlinic, published a paper on the use of galvanic currents to treat patients with age-related cortical cataract.…”
Section: Early Uses Of Electricity In Ophthalmologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 18th century, Benjamin Franklin reported that patients who were struck by lightning developed rapidly progressing cataracts, which ultimately resulted in blindness. 7 Despite this report, electric and magnetic therapy was practiced in London for the treatment of patients with cataract in 1779. 7 In 1887, Elliot Colburn, professor of ophthalmology and otology in the Chicago Policlinic, published a paper on the use of galvanic currents to treat patients with age-related cortical cataract.…”
Section: Early Uses Of Electricity In Ophthalmologymentioning
confidence: 99%
“…7 Despite this report, electric and magnetic therapy was practiced in London for the treatment of patients with cataract in 1779. 7 In 1887, Elliot Colburn, professor of ophthalmology and otology in the Chicago Policlinic, published a paper on the use of galvanic currents to treat patients with age-related cortical cataract. He suggested that patients without choroidal and retinal comorbidities and without systemic complications, such as diabetes, nephropathy, and cirrhosis, should expect to have visual improvement after receiving galvanic treatment.…”
Section: Early Uses Of Electricity In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Initially, surgeon John Syng Dorsey, Physick's nephew, had operated on Shaw 3 times using the method of division, which enjoyed widespread popularity during this period. 8,10 This method involved breaking the cataract with a needle so that the remnants could be absorbed by the natural inflammatory mechanism over a period of months. 11 Dorsey described his technique as follows: after dilating the pupil with stramonium, he introduced a needle through the cornea with which "the capsule and lens are to be torn in pieces: fragments of the lens can often be pushed forward into the anterior chamber of the eye, where they speedily dissolve."…”
Section: Introductionmentioning
confidence: 99%
“…Scudder first became known for producing and setting prosthetic eyes. Although others in America had set artificial eyes, 17 Scudder is the earliest identified oculist in America to produce them himself. He began this practice by 1823 or 1824, 18 although the prostheses were not advertised until 1827.…”
mentioning
confidence: 99%